Classic Morita Therapy: Advancing Consciousness in Psychotherapy - Peg LeVine (Psychotherapy and Counselling Journal of Australia)
This article chronicles "peripheral consciousness" and therapy developed by Japanese psychiatrist Shōma Morita, MD (1874-1938). As a contemporary of Freud, Morita challenged psychoanalysts who sanctioned an unconscious or unconsciousness (collective or otherwise) that resides inside the mind. From a human justice perspective, Morita’s formulation of consciousness releases clients from being solely responsible for their dysfunction. Morita was drawn to the earnest nature of analysts and how they strove to comprehend their patients’ anxieties and developmental histories. In fact, Morita developed his theories and methods with as much rigour as his Euro-American contemporaries, including Sigmund Freud, Wilfred Bion, Melanie Klein, Wilhelm Reich, Jean Charcot, Jacob Levy Moreno, Jacque Lacan, Carl Rogers, and Alfred Adler. In the early 1950s, especially, analyst Karen Horney progressed her grasp of Morita, Zen and psychotherapy while in Japan. Since cognitive science took hold in the 1970s, however, complex consciousness theories have lost footing in psychology and medical science. This article aims to reinstate "consciousness" as the dynamic core of Morita therapy. He advanced a phenomenal connexion between existentialism, Zen, Nature and the therapeutic role of serendipity; his views enhance Freud’s 1919 treatise on "The Uncanny". The presence or absence of a theory of consciousness sways how, what, and where we practice and conduct research, as well as case formulation and health promotion. Morita is our forerunner of Ecopsychology and pioneer in consciousness studies. Pointedly, he equalised the strength between human-to-human attachment and human-to-Nature bonds by penetrating our anthropomorphic borders.